Heart remodeling in patients with post-infarction cardiosclerosis at various stages of chronic heart failure - V. V. Masur; A. M. Kalinkin; O. A. Zamoraev; E. S. Masur (Российский кардиологический журнал, 2008)
The study investigated right ventricular (RV) remodeling during chronic heart failure (CHF) progression in patients with post-infarction cardiosclerosis (PICS). In total, 69 PICS patients and 14 healthy controls were examined. RV length and volume, its systolic and diastolic function were assessed by echocardiography method. At CHF Stages I-IIA, no substantial changes in RV volume and function were observed, but Stage I was characterized by significant RV length reduction, comparing to the controls. At CHF Stage IIB, RV length and volume were significantly increased, and systolic and diastolic dysfunction was observed. It could be concluded that RV remodeling in PICS patients starts at CHF Stage I already, due not to increased RV load, but to heart anatomy features, as interventricular septum is common for both ventriculi.